2022
DOI: 10.1038/s41467-022-29294-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for different types of hetero-tetrameric light-harvesting complexes in a diatom PSII-FCPII supercomplex

Abstract: Fucoxanthin chlorophyll (Chl) a/c-binding proteins (FCPs) function as light harvesters in diatoms. The structure of a diatom photosystem II-FCPII (PSII-FCPII) supercomplex have been solved by cryo-electron microscopy (cryo-EM) previously; however, the FCPII subunits that constitute the FCPII tetramers and monomers are not identified individually due to their low resolutions. Here, we report a 2.5 Å resolution structure of the PSII-FCPII supercomplex using cryo-EM. Two types of tetrameric FCPs, S-tetramer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 43 publications
1
41
3
1
Order By: Relevance
“…Absorption wavelength shift and light intensity: (a) low-light conditionChl c is deprotonated at high pH; (b) high-light conditionChl c is protonated at low pH, and the Soret and Q bands of Chl c are red-shifted. The cofactor arrangement of the PSII–FCP complex structure is shown . Note that Chl c 1 -303 and -309 in the PSII–FCP complex structure correspond to Chl c 1 and Chl c 2 in the isolated FCP crystal structure, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Absorption wavelength shift and light intensity: (a) low-light conditionChl c is deprotonated at high pH; (b) high-light conditionChl c is protonated at low pH, and the Soret and Q bands of Chl c are red-shifted. The cofactor arrangement of the PSII–FCP complex structure is shown . Note that Chl c 1 -303 and -309 in the PSII–FCP complex structure correspond to Chl c 1 and Chl c 2 in the isolated FCP crystal structure, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the LUMO and the LUMO+1 are delocalized toward the acrylate moiety only when the acrylate moiety is protonated, leading to stabilizations of the LUMO and the LUMO+1 and an increase in the absorption wavelength (Figure 7c). Although Chlcs are located only on the stromal side in the FCP crystal structure from Phaeodactylum tricornutum (Figure 1b), 4 cryo-electron microscopic analysis showed that Chlcs are also located on the lumenal side of the photosystem II−FCP (PSII−FCP) complex structure from the diatom Chaetoceros gracilis 8 (Figure 8). In photosynthesis, protons are released toward the lumenal side of the thylakoid membrane of chloroplasts, and the pH values on the lumenal side decrease as the reaction proceeds.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that there are two types of FCP-A tetramer found in C. gracilis, one strongly associated (Stetramer) with the PSII core and the other moderately associated (M-tetramer), and only the latter one contains diadinoxanthin (Dd). 27 Thus, our sample of FCP-A represents more of the S-tetramer. The fluorescence emission spectra at 77 K (Figure 1C) of the two complexes exhibit large differences, with FCP-B/C emission peaking at 676 nm and FCP-A at 684 nm.…”
Section: T H Imentioning
confidence: 99%